Comparação das respostas cardiovasculares durante o exercício com intensidade recomendada pelas diretrizes versus exercício com intensidade autosselecionada em pacientes com doença arterial periférica: um estudo randomizado crossover - Faria, Deivide Rafael Gomes de (2023)
Although the benefits of supervised walking training in patients with peripheral arterial disease (PAD) and symptoms of intermittent claudication (IC) are well established, one of the main problems encountered in this type of protocol is low adherence to training, which is possibly related to the exercise-induced pain. Exercises with self-selected intensity have emerged as an alternative in the treatment of some diseases with some benefits. The main advantage of this modality is that the patient selects the intensity of his choice. However, the characteristics of exercise at self-selected intensity in patients with PAD are still unknown. The aim of the present study was to describe cardiovascular responses during walking exercise at self-selected intensity on cardiovascular health indicators in patients with PAD and to compare them with the current exercise recommendation for these patients. For this purpose, 20 patients with PAD were randomly submitted to two experimental sessions: a self-selected session (SS: the participant chose speed and rest intervals) and a session recommended by the guidelines (SG: selected speed until the participant felt IC pain, with scheduled intervals). Both sessions had 30 minutes of active walking exercise. During the session, cardiovascular responses were obtained, systolic (SBP) and diastolic (DBP) blood pressure, heart rate (HR), rate pressure product (RPP), middle artery cerebral blood flow velocity (CBFV), left and right. Affective perceptual used were subjective perception of effort, pain and affection, as well as information about the exercises performed during the session. Responses during exercise were compared using the Wilcoxon test and correlation between affective and cardiovascular perceptual variables were analyzed using the Spearman test. A value of P<0.05 was considered significant. On average, during exercise, no significant differences were observed between SG and SS for all cardiovascular and affective variables. When the peak of responses was analyzed, SG showed higher values for HR [SG: 112 (47) vs. SS: 98 (32) bpm, p=0.026] and right CBFV [SG: 74 (28) vs. SS: 67 (36) cm/s, p=0.036]. The variation (Δ) between pre and peak moment was greater in SG in HR [SG: 31 (33) vs. SS: 30(18) bpm, p=0.020] and in RPP [SG: 7477 (6510) vs. 5804 (4237) bpm.mmHg, p=0.048]. Among the affective perceptual variables, the SG session had higher peak values [SG: 3 (2) vs. SS: 2 (2), p=0.015]. In SG, there was a relationship between cardiovascular variables and affective perceptual: SBP and pain (rho= -0.646; p=0.04); HR and pain (rho= -0.461; p=0.041); SG and pain (rho= -0.491; p=0.029); PAD and affection (rho= 0.438; p=0.053), and; Left CBFV and affect (rho= 0.684; p=0.029). In conclusion, on average, SS presented the same stimulus as SG in terms of affective and cardiovascular perceptual variables. At its peak, SS caused less pain and lower HR and RPP values when compared to SG, which may justify the preference for longer series and less rest stops. The perceptual affective and cardiovascular variables were only related in SG.